Character Education Building through Reciting Ṣalawāt - Abdullah Mu'min (International Journal of Nusantara Islam, 2017)
This paper tries to discuss about character education building through reciting ṣalawāt. By using literature study, this article found that character education building is an effort in dealing with behavioral and moral degradation problems in the midst of the generation of the nation today. One of the interventions that can be done is through repetition of ṣalawāt recitations that are internalized and interpreted as a way to connect to the figure of uswatun ḥasanah, perfecting human morals, which has a positive impact on physical and mental, also has the power to change deviant behavior. As a recommendation, this article states that there is no harm if the above findings are applied to Islamic education institutions